2024
DOI: 10.1245/s10434-023-14880-8
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarks in Liver Resection for Intrahepatic Cholangiocarcinoma

Laura Alaimo,
Yutaka Endo,
Giovanni Catalano
et al.

Abstract: Introduction Benchmarking in surgery has been proposed as a means to compare results across institutions to establish best practices. We sought to define benchmark values for hepatectomy for intrahepatic cholangiocarcinoma (ICC) across an international population. Methods Patients who underwent liver resection for ICC between 1990 and 2020 were identified from an international database, including 14 Eastern and Western institutions. Patients operated on at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
(55 reference statements)
0
1
0
Order By: Relevance
“… 2 , 3 The current study was important because we identified clinically relevant perioperative outcomes associated with curative-intent surgery for ICC and established benchmark values that can be applied across a heterogeneous population of centers. 4 …”
Section: Pastmentioning
confidence: 99%
“… 2 , 3 The current study was important because we identified clinically relevant perioperative outcomes associated with curative-intent surgery for ICC and established benchmark values that can be applied across a heterogeneous population of centers. 4 …”
Section: Pastmentioning
confidence: 99%